Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00464-007-9552-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of radical sigmoid colectomy performed as natural orifice translumenal endoscopic surgery (NOTES) using transanal endoscopic microsurgery

Abstract: It is possible to complete the critical steps of a NOTES sigmoid resection, en bloc lymphadenectomy, primary anastomosis, and retrieval of an intact specimen without any incisions using transanal endoscopic microsurgery instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
168
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(171 citation statements)
references
References 12 publications
0
168
0
3
Order By: Relevance
“…There are serious concerns that the conclusions of the published articles on TAMIS as a valid alternative to TEM are too optimistic. In fact, 30 years after its introduction into the clinical setting, TEM is not only the standard surgical treatment for benign polyps and early cancers of the rectum, it has also demonstrated several other features such as efficacy in achieving endoluminal circumferential resections up to complete colorectal procedures [19]. Until clinical trials on the topic are available and the safety of TAMIS is confirmed, TEM remains an unequaled tool for rectal surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…There are serious concerns that the conclusions of the published articles on TAMIS as a valid alternative to TEM are too optimistic. In fact, 30 years after its introduction into the clinical setting, TEM is not only the standard surgical treatment for benign polyps and early cancers of the rectum, it has also demonstrated several other features such as efficacy in achieving endoluminal circumferential resections up to complete colorectal procedures [19]. Until clinical trials on the topic are available and the safety of TAMIS is confirmed, TEM remains an unequaled tool for rectal surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…It immediately set off a worldwide quest to determine what types of operations could be mastered with the NOTES approach. Among these leaders was Mark Whiteford, who in collaboration with NOTES authority, Lee Swanström, successfully demonstrated that transanal TME could be completed using a TEM scope and without abdominal assistance in a cadaveric model [7]. Unlike Marks, Whiteford's objective was not improved access to the distal rectum, but rather the avoidance of abdominal access trauma (the very impetus behind NOTES) [6].…”
mentioning
confidence: 99%
“…Так, в 2007 г. M. Whiteford [33] сообщил о первой трансанальной резекции прямой кишки посред-ством использования платформы ТЭМ на трупах. Следующим этапом стало экспериментальное при-менение трансанальных резекций на животных [34].…”
Section: обзорыunclassified